Design of front-end electronics for HXI spectrometer flight model on-board ASO-S satellite. (1st February 2022) - Wan, Q.; Zhang, Y.; Guo, J.H.; Zhang, Y.Q.; Xu, X.
Abstract: Advanced Space-based Solar Observatory (ASO-S), developed by Chinese Academy of Sciences, is utilized for observing the solar magnetic field, coronal mass ejection, and solar flare, as well as studying the relationships among them. As one of the three scientific payloads on ASO-S, Hard X-ray Imager (HXI) is designed for solar hard X-ray imaging with outstanding temporal and spatial resolutions. The spectrometer is an important part of HXI and used to measure the incident photon with a dynamic range of 30–200 keV after Fourier modulation by the collimator. It consists of 99 detector units and front-end electronics (FEE). The FEE can process all the 99 detector units' signals independently in less than 2 μs. The noise of charge measure is less than 500 fC for a dynamic range of 20 pC–900 pC. In this paper, the implementation of FEE is introduced, including the design of electronics, quality control, and performance tests. All these tests show that the FEE can meet the HXI mission requirements.